Revisión de alcance de reportes de efectos adversos causados por vacunas contra el COVID - 19 (2024)
In this work, the aim was to establish the relationship between the implementation of COVID-19 vaccines and the quality of the bibliographic material published to date. A search was conducted in the PubMed database for meta-analyses addressing the safety of implementing vaccines to prevent SARS-CoV-2 infection, and the bibliographic material deemed appropriate was selected. This material was qualified using the AMSTAR tool to ensure the use of the best quality bibliography for the study. In the end, it was found that COVID-19 vaccination may be related to the presence of local and systemic adverse effects, in addition to increasing the risk of myocarditis, Bell's palsy, and thrombosis. However, it is considered that the benefits of vaccination outweigh the potential risks associated with it.